Does Wage Rank Affect Employees? Wellbeing? - Gordon D. A. Brown; Jonathan Gardner; Andrew J. Oswald; Jing Qian (Institute for the Study of Labor (IZA), 2005)
What makes workers happy? Here we argue that pure ?rank? matters. It is currently believed that wellbeing is determined partly by an individual?s absolute wage (say, 30,000 dollars a year) and partly by the individual?s relative wage (say, 30,000 dollars compared to an average in the company or neighborhood of 25,000 dollars). Our evidence shows that this is inadequate. The paper demonstrates that range-frequency theory – a model developed independently within psychology and unknown to most economists – predicts that wellbeing is gained partly from the individual?s ranked position of a wage within a comparison set (say, whether the individual is number 4 or 14 in the wage hierarchy of the company). We report an experimental study and an analysis of a survey of 16,000 employees? wage satisfaction ratings. We find evidence of rank-dependence in workers? pay satisfaction.
Keywords: J28; J30; 330; job satisfaction; wages; rank; wellbeing; Lohn; Erwerbsstatus; Arbeitszufriedenheit; Sozialpsychologie; Grossbritannien